HUMAN RESOURCE MANAGEMENT PRACTICES, SCHOOL INFRASTRUCTURE AND ACADEMIC PERFORMANCE OF SECONDARY SCHOOLS IN MACHAKOS COUNTY, KENYA - MUTUKU, AGNES WANZA (Machakos University Press, 2022)
Academic performance trend in K.C.S.E. in Machakos County has been on a declining trend in the recent past , hence the need for the study. The aim of the study was to establish the influence of Human Resource Management practices on academic performance of secondary schools in Machakos County. The study sought to examine the influence of teaching staff recruitment and selection, teaching staff training and development, teaching staff compensation and teaching staff safety on the academic performance of secondary schools in Machakos County, Kenya. The study also sought to establish whether school infrastructure moderated the relationship between Human Resource Management practices and academic performance of these schools. The Resource Based Theory, Universalistic Theory and the Human Capital Theory informed this study.The study was anchored on pragmatic paradigm and used mixed methods research design.The target population was 413 secondary schools in Machakos County. The school principals were selected as units of observation. Purposive sampling was used to select six secondary schools from where the key informants were drawn. These consisted of the two national, top two performing and bottom two non performing secondary schools in Machakos County. The rest of the schools were selected using stratified sampling based on the category of school where a sample size of 201 was obtained. The study used primary data collected using self-administered questionnaires and interview schedules. Qualitative data collected was analysed using content analysis while for the quantitative data, descriptive analysis and inferential analysis were carried out. Both bivariate and multivariate regression analyses were conducted to determine the relationship between the study variables. The findings of the study were that Human Resource Management practices under study namely teaching staff recruitment and selection, teaching staff training and development, teaching staff compensation and teaching staff safety positively and significantly influenced the academic performance of secondary schools in Machakos County. The findings showed that school infrastructure significantly moderated the relationship between Human Resource Management practices and the academic performance of the schools where it strengthened the influence that these practices had on the academic performance of the schools. Therefore, the study concluded that Human Resource Management practices were significant variables that influenced the academic performance of secondary schools in Machakos County and hence, when evaluating the factors likely to impact the academic performance of these schools, it is prudent for the schools‘ management to take in to account these practices. The study also concluded that when the different infrastructural priority areas for the schools were addressed, it was likely that the effectiveness of different Human Resource Management practices in yielding better academic performance in these schools would be enhanced. Several recommendations for improvement were made, key among them that: The Teachers Service Commission ought to continuously and regularly review the compensation packages for teachers so that they are at all times competitive and also market based. For the private schools, the study recommends for diversification of income streams by the schools‘ management so that the compensation packages given to their teachers are competitive. The study recommends that schools‘ management should also develop operational policies to guide the design of their training and career development programs to make them more inclusive, relevant and comprehensive. The study recommends that the Ministry of Education should design frameworks and offer assistance required by secondary schools to set up efficient safety and security systems in schools and champion for more budgetary allocations from the government in order to increase funding required for infrastructural development in public schools. For private schools, the study recommends that the government should enforce policies that compel these schools to have the requisite basic school infrastructure required by students to adequately prepare for examination.